A novel method for metal–diamond composite coating deposition with cold spray and formation mechanism. (1st April 2016) - Aldwell, Barry; Yin, Shuo; McDonnell, Kevin A.; Trimble, Daniel; Hussain, Tanvir; Lupoi, Rocco
Abstract: This paper describes the application of cold spray to the deposition of a diamond grade pre-coated with Cu and Ni. This is the first time that pre-coated diamond powders are used as the sole feedstock without the addition of binders (ductile phases) in cold spraying. The experimental results showed that it was possible to manufacture thick metal–diamond composite coatings onto an Al alloy substrate with high diamond fraction in the coating and without phase change. Results from this paper also have demonstrated a new methodology for the deposition of metal–diamond/ceramic composite coating with the cold spray technique. Graphical abstract: